If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -10 = 7x + -16 Reorder the terms: -10 + 4x = 7x + -16 Reorder the terms: -10 + 4x = -16 + 7x Solving -10 + 4x = -16 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -10 + 4x + -7x = -16 + 7x + -7x Combine like terms: 4x + -7x = -3x -10 + -3x = -16 + 7x + -7x Combine like terms: 7x + -7x = 0 -10 + -3x = -16 + 0 -10 + -3x = -16 Add '10' to each side of the equation. -10 + 10 + -3x = -16 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = -16 + 10 -3x = -16 + 10 Combine like terms: -16 + 10 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 2(150-0.5y)+y=300 | | -14=-7v | | 6a-9=3a+6 | | 80-(4x+15)=4(x+5)+x | | (2x-4)+9i=8+3i | | -32=3+9(f+5) | | 2y-2y=14+4y | | 4t-4=2t-2 | | 3a-12=6a-21 | | 8k+8(k-1)=5k+36 | | 13x-7x-35=6x-35 | | 2a+14=5a+5 | | Y=x^2-9x+8 | | 2g+14+5g-8g=3+8 | | 6t+12=18 | | 7(1-3n)-2n=-85 | | 5y^2-12y+5=0 | | 2g+14+5g-8g=3-8 | | (6x+2)(x-3)=0 | | 3w-8=7w | | y=0.5+b | | 2*x^3-3*x^2-72*x+3=0 | | 7p+4=67 | | 6r+9=63 | | t^2(t^2-5)=2t^2-5 | | 6x+1y=30 | | (2r+2r)=96 | | 3r-5=0 | | 12+14=-7(x-4)+8x | | 0.36y=1 | | 3x+17=74 | | -2x+8=x+29 |